Effectiveness of postoperative radiotherapy after radical cystectomy for locally advanced bladder cancer. (22nd May 2019) - Fischer‐Valuck, Benjamin W.; Michalski, Jeff M.; Mitra, Nandita; Christodouleas, John P.; DeWees, Todd A.; Kim, Eric; Smith, Zachary L.; Andriole, Gerald L.; Arora, Vivek; Bullock, Arnold; Carmona, Ruben; Figenshau, Robert S.; et al.
Abstract: Background: Local‐regional failure (LF) for locally advanced bladder cancer (LABC) after radical cystectomy (RC) is common even with chemotherapy and is associated with high morbidity/mortality. Postoperative radiotherapy (PORT) can reduce LF and may enhance overall survival (OS) but has no defined role. We hypothesized that the addition of PORT would improve OS in LABC in a large nationwide oncology database. Methods: We identified ≥ pT3pN0‐3M0 LABC patients in the National Cancer Database diagnosed 2004‐2014 who underwent RC ± PORT. OS was calculated using Kaplan‐Meier and Cox proportional hazards regression modeling was used to identify predictors of OS. Propensity matching was performed to match RC patients who received PORT vs those who did not. Results: 15, 124 RC patients were identified with 512 (3.3%) receiving PORT. Median OS was 20.0 months (95% CI, 18.2‐21.8) for PORT vs 20.8 months (95% CI, 20.3‐21.3) for no PORT ( P = 0.178). In multivariable analysis, PORT was independently associated with improved OS: hazard ratio 0.87 (95% CI, 0.78‐0.97); P = 0.008. A one‐to‐three propensity match yielded 1, 858 patients (24.9% receiving PORT and 75.1% without). In the propensity‐matched cohort, median OS was 19.8 months (95% CI, 18.0‐21.6) for PORT vs 16.9 months (95% CI, 15.6‐18.1) for no PORT ( P = 0.030). In the propensity‐matched cohort of urothelial carcinoma patients (N = 1, 460), PORT was associated with improved OS for pT4, pN+, and positive margins ( P < 0.01 all). Conclusion: In this observational cohort, PORT was associated with improved OS in LABC. While the data should be interpreted cautiously, these results lend support to the use of PORT in selected patients with LABC, regardless of histology. Prospective trials of PORT are warranted. Abstract : In this analysis of the National Cancer Database that included 15, 124 patients with ≥ pT3pN0‐3M0 disease, 512 who received PORT, the use of PORT was associated with an overall survival (OS) benefit on Cox multivariable analysis (HR 0.87 (95% CI, 0.78‐0.97); P = 0.008). In the propensity‐matched cohort, median OS was 19.8 months for PORT vs 16.9 months for no PORT ( P = 0.030).